Sedentary behaviour associations with health outcomes in people with severe mental illness: a systematic review. (21st February 2019) - Bort-Roig, Judit; Briones-Buixassa, Laia; Felez-Nobrega, Mireia; Guàrdia-Sancho, Anna; Sitjà-Rabert, Mercè; Puig-Ribera, Anna
Abstract: Background: Although people with severe mental illness (SMI) show high sedentary behaviour (SB) levels, there is little research on how SB patterns influence health and which type of intervention is the most critical for reducing this behaviour. The aims of this study are to examine associations between SB and physical and mental health in people with SMI; and the extent to which physical activity interventions may effectively reduce SB. Methods: This systematic review was conducted according to the PRISMA guidelines. Experimental and observational studies were searched in Medline, PsycInfo, Embase, CINHAL and Scopus up to June 2018. Eighteen studies ( n = 15 observational; n = 3 experimental) met the inclusion criteria. Results: Both subjective and objective measurements for SB (an average of 8.5 and 10 h day −1, respectively) were positively associated with an increased cardiovascular and metabolic risk, worse global functioning, less quality of life, more severity of depressive symptoms, longer illness duration and higher doses of antipsychotic medication. Regarding intervention studies, active-lifestyle interventions ( n = 2) reduced sedentary time (1.7–2.4 h day −1 ) while structured exercise ( n = 1) reported no changes on SB. Conclusions: Levels of sedentariness in people with SMI are linked to an increased physical health risk, worse wellbeing and poorer mental health. Active-lifestyle interventions may be an indicated approach to reduce SB of people with SMI. However, a limited number of studies, their mixed quality and the heterogeneity of health outcomes made it difficult to provide robust conclusions on SB effects in people with SMI. Study protocol was registered to PROSPERO (CRD42017067592).